Pengembangan Kreativitas Anak Usia Dini melalui Origami - Uswatun Hasanah; Dian Eka Priyantoro (Jurusan PGMI FTIK IAIN Metro Lampung, 2019)
Everyone has different abilities. Reflecting from the diversity of different abilities, it should be necessary to do various ways in developing those abilities. One of the individual's abilities is creativity. Creativity is an important ability to develop, even in various elements of education. In this case, educators play an important role to develop that ability. Creativity is very important to develop, because creativity has a big influence and adequate to contribute in one's life, for example in academic achievement. The art of paper folding or origami, is an excellent activity to stimulate creativity as well as build a structured mind power in children. Because the subject of this activity is an early childhood, then this activity is designed with a simple method. Children who follow this activity are only told to look, then practice together and they may even form another pattern they want.